2002
DOI: 10.1105/tpc.003038
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Actin Organization by Actin-Depolymerizing Factor in Elongating Pollen Tubes[W]

Abstract: Pollen tube elongation is a polarized cell growth process that transports the male gametes from the stigma to the ovary for fertilization inside the ovules. Actomyosin-driven intracellular trafficking and active actin remodeling in the apical and subapical regions of pollen tubes are both important aspects of this rapid tip growth process. Actin-depolymerizing factor (ADF) and cofilin are actin binding proteins that enhance the depolymerization of microfilaments at their minus, or slow-growing, ends. A pollen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
245
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(258 citation statements)
references
References 71 publications
13
245
0
Order By: Relevance
“…33 To examine whether they also contained other transcripts, RT-PCR analysis was performed. Several tobacco pollen-specific genes were tested including profilin, 39 actin depolymerizing factor 1 (ADF1), 40 eukaryotic translation initiation factors eIF4E, eIFiso4E 41 and R-tubulin A1 (accession number AJ421411; D. Brevario, direct submission). RT-PCR analysis revealed that all tested transcripts were present in the EPP fractions isolated by ultracentrifugation as well as directly from SEC ( Figure 3).…”
Section: Epps Contain Different Mrnasmentioning
confidence: 99%
“…33 To examine whether they also contained other transcripts, RT-PCR analysis was performed. Several tobacco pollen-specific genes were tested including profilin, 39 actin depolymerizing factor 1 (ADF1), 40 eukaryotic translation initiation factors eIF4E, eIFiso4E 41 and R-tubulin A1 (accession number AJ421411; D. Brevario, direct submission). RT-PCR analysis revealed that all tested transcripts were present in the EPP fractions isolated by ultracentrifugation as well as directly from SEC ( Figure 3).…”
Section: Epps Contain Different Mrnasmentioning
confidence: 99%
“…These actin phenotypes are accompanied by either a reduction or stimulation of cell growth, respectively. In another study, over-expression of a pollen-specific ADF from tobacco, NtADF1, noticeably reduces the number of long axially oriented actin bundles in the pollen tube shank [Chen et al, 2002]. Regarding tip-growth, the subapical cortical fringe composed of parallel short bundles is unable to form in tip-growing moss protonema cells lacking ADF function [Augustine et al, 2008].…”
Section: Actin Bundling Versus Depolymerization Forcesmentioning
confidence: 97%
“…The apex of the pollen tube is submitted to constant changes in ionic conditions, including a fluctuating apical Ca 21 gradient and a subapical alkaline region [Holdaway-Clarke and Hepler, 2003;, which regulate actin cytoskeleton dynamics and organization by the activation/inactivation of ABPs [Ren and Xiang, 2007]. As an example, ADF predominantly localizes to the subapical region, where its fragmenting activity is stimulated by alkaline pH conditions [Chen et al, 2002;Lovy-Wheeler et al, 2006]. Given the high degree of actin cytoskeleton remodeling in the subapical region, the series of subapical actin structures reported so far has been suggested to belong to a continuum of structural configurations that interconvert from one to another during pollen tube growth.…”
Section: Actins Bundles In Tip-growing Cellsmentioning
confidence: 99%
“…In the shank region, longitudinal actin cables exist throughout the cytoplasm, facilitating the transport of organelles and vesicles between the shank region and the subapex to support the reverse-fountain cytoplasmic streaming pattern (Ye et al, 2009;Cheung et al, 2010;Zheng et al, 2013;Duckney et al, 2017;Qu et al, 2017). At the subapex, actin filaments form regular structures in different species, such as the collar, fringe, mesh, or funnel, and some observations indicated that subapical F-actin could regulate the accumulation of vesicles and the growth of the tip region (Gibbon et al, 1999;Fu et al, 2001;Vidali et al, 2001;Chen et al, 2002;LovyWheeler et al, 2005;Qu et al, 2017). At the apex, actin filaments are generally less abundant but are highly dynamic with dense actin structures, which mediates the interaction between the apical/subapical PM and the cytoplasm during rapid tube elongation (Fu et al, 2001; Lee and Yang, 2008;Cai and Cresti, 2009;Cheung et al, 2010;Qu et al, 2013;Rounds et al, 2014;Zhou et al, 2015;Qu et al, 2017).…”
mentioning
confidence: 99%